STRESS RELATIONSHIP WITH ELDERLY IN MEETING THE SLEEPING VILLAGE DISTRICT KEBONAGUNG PADANGAN BOJONEGORO - RAHMA, RAHMAWATI; N, SITI; Z, AZUMA (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2016)
Stress is a non-specific reaction of humans to stimuli. rest and sleep is a basic need that is needed by everyone. In the village Kebonangung in need get a lot of elderly people who sleep less than 6 hours / day. This is partly due to natural stress in the elderly. To determine the relationship of stress to the fulfillment of the elderly in the village sleeping Kebonagung District of Bojonegoro Padangan.        Iin this study using analytical survey. Independent research variable is the level of stress that is the fulfillment of the elderly and dependent elderly sleep. Data collection using questionnaires. Statistical tests using chi-square and contingency coefficient. Results of statistical analysis Chi-Square test showed that the value of ? <0.05 is equal to 0.000 to 0.610 association flatness level so that H0 is rejected with a mean degree of flatness of the relationship is no relationship with the level of stress in the elderly sleep fulfillment Kebonagung Village District of Bojonegoro Padangan.        It can be concluded over the majority of respondents did not experience major stres.Sebagian tidurnya.Ada respondents met the needs of the relationship of stress to the fulfillment of the elderly in the village sleeping Kebonagung District of Bojonegoro Padangan 2014 Expected for respondent should maintain the physical condition and the condition of mind in a relaxed state to avoid stress that can lead to sleep problems